Mussel inspired bacterial denitrification of water using fractal patterns of polydopamine. (February 2020) - Boroumand, Yasaman; Razmjou, Amir; Moazzam, Parisa; Mohagheghian, Fereshteh; Eshaghi, Ghazaleh; Etemadifar, Zahra; Asadnia, Mohsen; Shafiei, Rasoul
Graphical abstract: Highlights: Polydopamine (PDA) established a fractal pattern on polyethersulfone (PES) surface. The fractal pattern formed a combination of hydrophilic and hydrophobic regions. Pseudomonas stutzeri was immobilized on PDA modified PES surface. Bacterial immobilization process was applied to nitrate removal of water. Nitrate removal was carried out under optimum situations. Abstract: Nitrate is currently one of the most significant causes of water pollution in many parts of the world due to its detrimental effects on humans and the environment. The purpose of this study was to find a novel immobilization method based on bacterial adsorption to adhesive coating material, for use in water denitrification. The fractal formation capability of polydopamine (PDA) allowed coating of the surface of in-house asymmetric polyethersulfone (PES) beads (1.65–2.35 mm in diameter), and immobilizing the denitrifying bacteria Pseudomonas stutzeri with noticeable denitrification potential, on the surface of hyper-branched PDA coated beads. For surface characterization, SEM, wettability measurement, and ATR-FTIR spectroscopy were performed. Nitrate and nitrite concentrations were measured by APHA standard method 4500-NO3 − -B and a colourimetric method using two reagents respectively. The effects of temperature, pH and different carbon sources (Acetic acid, methanol, and ethanol) on the denitrification process were also investigated. The results revealed that the bacterial immobilization on PES surface with fractal patterns of PDA (with fractal dimension (Df) value of 1.57) was successful, and the optimum parameters for nitrate removal were established as 25 °C, pH = 8, and 420 mg/L ethanol as the carbon source. Finally, this research showed that under the optimum conditions the immobilized bacteria exhibited 100 % removal efficiency for 28 mg of NO3 –N in 22 h (removal rate: 8.06 mg NO3 -N/h/mg biomass of bacteria). We found that the immobilization of bacteria on the PDA coated beads is practicable and that the denitrification rate is adequate.